GAMBARAN PENYIMPANAN PERBEKALAN FARMASI DI GUDANG FARMASI RUMAH SAKIT BHAYANGKARA MANADO - Ayhuan, Jeckson; Citraningtyas, Gayatri; Jayanto, Imam (UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTThe storage of pharmaceutical supplies must ensure the quality and safety of pharmaceutical preparations, medical devices and consumable medical materials in accordance with pharmaceutical needs. This study aims to obtain an overview of the storage of pharmaceutical supplies in the Bhayangkara Hospital Manado warehouse based on the Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016. In the research results found indicators of strengths, weaknesses, opportunities and threats. Indicators of strength are a well-organized system for arranging goods in a warehouse, supporting facilities in a well-functioning warehouse, a strategic location and a person in charge of pharmaceutical personnel. Weaknesses are the number of human resources that are still lacking and there are frequent power outages. The opportunity identified was the development of an up-to-date management information system. Threats include regulations from distributors of non-returnable goods and demand for goods during the night shift that cannot be fulfilled because warehouse operating hours end at 17.00. Keywords: Storage, Medicine, Hospital Pharmacy Installation ABSTRAKPenyimpanan perbekalan farmasi harus menjamin mutu dan keamanan sediaan farmasi, alat kesehatan dan bahan medis habis pakai yang sesuai dengan kebutuhan kefarmasian.Penelitian ini bertujuan untuk memperoleh gambaran tentang penyimpanan perbekalan farmasi di gudang RS Bhayangkara Manado berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 72 Tahun 2016. Dalam hasil penelitian ditemukan indikator kekuatan, kelemahan, peluang dan ancaman. Indikator kekuatan yaitu sistem penataan barang di gudang yang tertata dengan baik, fasilitas penunjang di gudang yang berfungsi dengan baik, lokasi yang strategis dan penanggung jawab tenaga kefarmasian. Kelemahan yaitu jumlah sumber daya manusia yang masih kurangan dan sering terjadi pemadaman listrik. Peluang yang ditemukan adalah pengembangan sistem informasi manajemen yang selalu diperbaharui. Ancaman antara lain regulasi dari distributor barang yang tidak dapat dikembalikan dan permintaan barang pada saat shift malam tidak dapat dipenuhi karena jam operasional gudang berakhir pada pukul 5 sore.. Kata kunci: Penyimpanan, Obat, Instalasi Farmasi Rumah Sakit